STRATEGI KOMUNIKASI KOTA BANDUNG DALAM MEMBENTUK CITY BRANDING SEBAGAI DESTINASI WISATA BELANJA - Astuti, Marhanani Tri (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
The city of Bandung has a compelling positive image as a tourist destination for shopping, therefore, Bandung performs communication strategies in developing the city branding as a shopping destination. The purpose of this study is to communicate the policies of Bandung City Government related to city branding and shopping destination. In line with the research problems and existing conditions, this research is a construction of a tourism phenomenon from the perspective of bureaucratic communication. Paradigmatically, this study will in nature be constructive as well as interpretative. The research concludes that Bandung City communication strategies have been built in developing the city branding as a shopping destination. At the level of primary communication, namely on the Government side, branding Bandung as a tourist city should refer to the branding policy of the Ministry of Tourism, as it is centralized. This branding represents Bandung’s character, potentials, and varied shopping attractions, as well as the people. Communication strategies undertaken by Bandung Tourism Office cover the operational strategy, persuasive and educative strategy, as well as collaborative strategy. This research recommends that the creation of brand logo and tagline should be followed by further exploration of the meaning.